Manajemen Kesantunan Berbahasa Dalam Aplikasi WAG Sebagai Sarana Komunikasi Kegiatan Pembelajaran - Elviria, Samia; Latief, Suryawahyuni (Attractive : Innovative Education Journal, 2022)
This study aims to describe how language politeness management in the student WAG application responds to messages delivered by lecturers and messages delivered by classmates carried out on communication science students in the odd semester of 2021/2022 guided by the principle of language politeness, namely the principle of politeness and the principle of politeness management. This research uses a qualitative descriptive research method with data collection through observation of activities in the WhatsApp Group (WAG) and messages contained in the WAG, interviews conducted with students are open, and documentation in the form of achievements in the WAG. The data collected carried out data analyzed through the stages of qualitative data analysis and the validity of the data was carried out through triangulation. The results showed that: 1) students prioritize the principles and rules of language politeness in responding to messages conveyed by lecturers rather than messages delivered by classmates, and 2) language politeness management is more applied to messages sent to lecturers than classmates are.